Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Sure, I'll walk you through the step-by-step solution to find the limit \(\lim _{x \rightarrow 3} \frac{x^3 - 27}{x - 3}\) using L'Hôpital’s rule.
1. Identify the Indeterminate Form:
First, we need to check whether the given limit results in an indeterminate form. Substitute \(x = 3\) into the expression:
[tex]\[ \frac{3^3 - 27}{3 - 3} = \frac{27 - 27}{0} = \frac{0}{0} \][/tex]
Since this is an indeterminate form of the type \(\frac{0}{0}\), we can apply L'Hôpital's rule.
2. Apply L'Hôpital's Rule:
L'Hôpital's rule states that if \(\lim_{x \to a} \frac{f(x)}{g(x)}\) results in \(\frac{0}{0}\) or \(\frac{\infty}{\infty}\), then this limit can be evaluated as:
[tex]\[ \lim_{x \to a} \frac{f(x)}{g(x)} = \lim_{x \to a} \frac{f'(x)}{g'(x)} \][/tex]
where \(f'(x)\) and \(g'(x)\) are the derivatives of \(f(x)\) and \(g(x)\), respectively.
Here, \(f(x) = x^3 - 27\) and \(g(x) = x - 3\).
3. Differentiate the Numerator and Denominator:
Now, we calculate the derivatives of the numerator and the denominator.
- Derivative of the numerator \(f(x) = x^3 - 27\):
[tex]\[ f'(x) = \frac{d}{dx}(x^3 - 27) = 3x^2 \][/tex]
- Derivative of the denominator \(g(x) = x - 3\):
[tex]\[ g'(x) = \frac{d}{dx}(x - 3) = 1 \][/tex]
4. Substitute the Derivatives:
Substitute \(f'(x)\) and \(g'(x)\) back into the limit:
[tex]\[ \lim_{x \to 3} \frac{f(x)}{g(x)} = \lim_{x \to 3} \frac{x^3 - 27}{x - 3} = \lim_{x \to 3} \frac{3x^2}{1} \][/tex]
5. Evaluate the New Limit:
Finally, we evaluate the limit by substituting \(x = 3\):
[tex]\[ \lim_{x \to 3} \frac{3x^2}{1} = \frac{3(3)^2}{1} = \frac{3 \cdot 9}{1} = 27 \][/tex]
Therefore, the limit is:
[tex]\[ \lim_{x \to 3} \frac{x^3 - 27}{x - 3} = 27 \][/tex]
1. Identify the Indeterminate Form:
First, we need to check whether the given limit results in an indeterminate form. Substitute \(x = 3\) into the expression:
[tex]\[ \frac{3^3 - 27}{3 - 3} = \frac{27 - 27}{0} = \frac{0}{0} \][/tex]
Since this is an indeterminate form of the type \(\frac{0}{0}\), we can apply L'Hôpital's rule.
2. Apply L'Hôpital's Rule:
L'Hôpital's rule states that if \(\lim_{x \to a} \frac{f(x)}{g(x)}\) results in \(\frac{0}{0}\) or \(\frac{\infty}{\infty}\), then this limit can be evaluated as:
[tex]\[ \lim_{x \to a} \frac{f(x)}{g(x)} = \lim_{x \to a} \frac{f'(x)}{g'(x)} \][/tex]
where \(f'(x)\) and \(g'(x)\) are the derivatives of \(f(x)\) and \(g(x)\), respectively.
Here, \(f(x) = x^3 - 27\) and \(g(x) = x - 3\).
3. Differentiate the Numerator and Denominator:
Now, we calculate the derivatives of the numerator and the denominator.
- Derivative of the numerator \(f(x) = x^3 - 27\):
[tex]\[ f'(x) = \frac{d}{dx}(x^3 - 27) = 3x^2 \][/tex]
- Derivative of the denominator \(g(x) = x - 3\):
[tex]\[ g'(x) = \frac{d}{dx}(x - 3) = 1 \][/tex]
4. Substitute the Derivatives:
Substitute \(f'(x)\) and \(g'(x)\) back into the limit:
[tex]\[ \lim_{x \to 3} \frac{f(x)}{g(x)} = \lim_{x \to 3} \frac{x^3 - 27}{x - 3} = \lim_{x \to 3} \frac{3x^2}{1} \][/tex]
5. Evaluate the New Limit:
Finally, we evaluate the limit by substituting \(x = 3\):
[tex]\[ \lim_{x \to 3} \frac{3x^2}{1} = \frac{3(3)^2}{1} = \frac{3 \cdot 9}{1} = 27 \][/tex]
Therefore, the limit is:
[tex]\[ \lim_{x \to 3} \frac{x^3 - 27}{x - 3} = 27 \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.